Microdistribuição e compartilhamento de hábitat dos caranguejos Panopeus americanus de Saussure, 1857 e Panopeus occidentalis de Saussure, 1857 (Decapoda: Panopeidae) na zona intermareal estuarina de Cananéia, São Paulo - Saraiva, Gabriel Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In the presente study, the spatial microdistribution patterns of the Panopeidae crabs Panopeus americanus and Panopeus occidentalis were analyzed. Thus, the sex ratio by size class, the effect of intertidal zones on the distribution and abundance of the species’ demographic classes and the occurrence of habitat sharing were investigated. The collections took place monthly from April 2015 to March 2016 in the intertidal region of Cananéia, South coast of São Paulo. In each sample, individuals were sexed according to the morphology of their abdômen. Crabs were quantified in each intertidal zone. Data were tested for normality. The sex ratio was assessed using the chi-square test. The effect of intertidal zones on distribution and abundance was analyzed using a generalized linear model. The similarity along the intertidal zone was also analyzed. Panopeus americanus presented high abundance and smaller average size in relation to P. occidentalis. From this study, it was revealed that P. americanus and P. occidentalis have a preference in the occupation of the high intertidal zone, probably related to the availability of micro-habitats. The data obtained by the presente study allow a better understanding of the life history of both species, in addition to serving as a parameter for future comparisons and monitoring of populations, as well as the ecosystem in wich they inhabit.

No presente estudo, foram analisados os padrões de microdistribuição espacial das espécies de caranguejos Panopeidae Panopeus americanus e Panopeus occidentalis. Sendo assim, a proporção sexual por classe de tamanho, o efeito das zonas intermareais na distribuição e abundância das classes demográficas das espécies e a ocorrência de compartilhamento de habitat foram averiguados. As coletas ocorreram mensalmente de abril de 2015 a março de 2016 na região intermareal de Cananéia, litoral sul de São Paulo. Em cada amostra, os indivíduos foram sexados de acordo com a morfologia do seu abdômen. Os caranguejos foram quantificados em cada zona intermareal. Os dados foram testados quanto à normalidade. A proporção sexual foi avaliada por meio do teste do qui-quadrado. O efeito das zonas intermareais na distribuição e abundância foi analisado através de um modelo linear generalizado. A similaridade ao longo da zona intermareal também foi analisada. Panopeus americanus apresentou maior abundância e menor tamanho médio em relação à P. occidentalis. A partir deste estudo, foi revelado que P. americanus e P. occidentalis possuem preferência na ocupação da zona alto intermareal, provavelmente relacionado à disponibilidade de micro-habitats. Os dados obtidos pelo presente estudo permitem maior compreensão de um importante aspecto da história de vida de ambas as espécies, além de servirem como parâmetro para futuras comparações e monitoramento das populações, bem como do ecossistema em que elas habitam.
Microdistribution and habitat sharing of Panopeus americanus de Saussure, 1857 and Panopeus occidentalis de Saussure, 1857 (Decapoda: Panopeidae) in the estuarine intertidal zone of Cananéia, São Paulo
Keywords: Mangrove; Crabs; Caranguejos; Animais do manguezal; Panopeidae